SUBLIMINAL MESSAGE OF NAZISM IDEOLOGY IN COMEDY-SATIRE FILM “JOJO RABBIT” - Mappatadang, Andi Siti Nurhaliza; Abdullah, Abdullah; Fitriyani, Fitriyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research is titled “Subliminal Message of Nazism Ideology in Comedy-Satire Film JoJo Rabbit.” Using a qualitative approach and semiotic analysis method, this study reveals how the elements of the film subtly convey Nazism ideology through its narrative, characters, and visual symbols. This research uses a descriptive qualitative method. The data of this study was carried out through direct interviews with viewers who had watched the film "Jojo Rabbit." These interviews were conducted over approximately three days, where respondents were asked to provide their views and interpretations regarding the film's elements related to Nazism ideology. The data obtained from these interviews were analyzed using semiotic theory to identify and interpret the signs and symbols present in the film. Additionally, relevant literature references were used to enrich the analysis and provide historical and theoretical context. The results of the study indicate that although "Jojo Rabbit" is packaged in the comedy-satire genre, the film effectively communicates criticism of Nazism ideology. The use of humor and irony in this film not only entertains but also invites viewers to reflect on the dangers and absurdities of the ideology. This research contributes to the understanding of how films can be used as a tool to convey ideological messages in a subtle and profound way. It is hoped that this research can provide new insights for readers and other researchers in the field of film and communication studies.Keywords: Subliminal Message; Nazism Ideology; Comedy-Satire Film